Niedoceniane czynniki znaczące w decyzjach edukacyjnych i życiowych współczesnej młodzieży gimnazjalnej = Undervalued factors influencing education and life decisions of present day middle schoolers - Zajdel, Krzysztof (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper is an attempt at answering the question of what are the possible education paths and possibilities of their realization in countryside middle schools; who supports the adolescent; how the future is planned along with the conditions necessary to succeed.
Keywords: młodzież gimnazjalna; gimnazjaliści; wybory życiowe; wybory edukacyjne